SELF-REGULATED LEARNING THROUGH ePORTFOLIO: A META-ANALYSIS (Malaysian Journal of Learning and Instruction, 2021)
Purpose: Self-regulated learning (SRL) has been established in the literature as beneficial for students in language learning. It is believed that SRL promotes learner autonomy and successful academic outcomes. Although SRL strategies are quite popular and heavily researched, their functionality through the medium of ePortfolio is uncertain. Therefore, this research analysed how SRL contributes to positive academic outcomes with ePortfolio as a medium.Methodology: A meta-analysis was carried out to identify the patterns and gaps in this research area. A total of 204 studies were identified based on a keyword search related to SRL and portfolio. These studies were further analysed to fit the criteria set for this research. Only nine studies fulfilled these criteria and were thus selected for the study. Findings: It was found that all nine studies included in this review emphasised different research methods and reported significant changes in students’ academic outcomes. Eight of the studies were quantitative in nature, while only one study was qualitative. Based on our interpretive findings, three themes were discovered, namely metacognition, collaboration and motivation.Significance: By clarifying the roles played by SRL and how ePortfolio as a tool can promote SRL, this study offers insights to those who wish to use ePortfolio as a medium to foster self-regulated learning. The results of the meta-analysis may also help researchers to explore this area of study and address research gaps in relatable contexts.